Centring sexual violence victims: what role for rape victim impact assessments? - Friskney, Ruth (International review of victimology, 2025)
In the light of the ongoing failures of the criminal justice system to tackle sexual violence, in particular the systematic injustices experienced by victims, we suggest the introduction of ‘Rape Victim Impact Assessments’ to centre victims’ rights and interests in the policy development and strategic governance of criminal justice systems. Impact assessments provide a framework for the systematic and evidence-based consideration of a new or change in policy, procedure, or practice. Building on the framework of impact assessments generally, and workshops with experts in policing sexual violence, this article discusses the development of a Rape Victim Impact Assessment tool in the context of policing sexual violence as part of the Home Office funded Operation Soteria in England. It also suggests lessons for criminal justice agencies to improve the development of victim-centred policies, procedures and practices.